Parent’s Interest Towards Developing Apps as a Tool for Student’s Control in Physical Education and Support Communication with Teacher - Wahyu Ragil Kurniawan; Ipang Setiawan; Donny Wira Yudha Kusuma; Dwi Gansar Santi Wijayanti (Universitas Negeri Semarang, 2023)
This study was conducted to find out parent’s interest in developing cellular-based application designs that make it easier for them to monitor their children's performance in school, especially in physical education. This study was conducted on parents, by paying attention to their experiences in using application products. The methods used in this study is a case study with descriptive qualitative research. The data has been analyzed through the stages:: Data Collection, Data Reduction, Data Presentation, and data Verification. The results in this study are the responses of the parents regarding the application designed to control students performance in physical education based on test the number of percentage show 90,39% are strongly agree with this design. Based on these results, it can show that parents are very supportive of the development of a prototype or a model that is used to support the learning process of children in schools, especially in physical education, and they need it. The conclusion is that cellular-based apps can be an innovative medium to intervene in changes and students' abilities in physical education learning. Parents really need the development of apps-based technology to make it easier for them to supervise their children during the physical education learning. This research can be used as the basis information for further research to create or develop more mobile applications or web based apps in physical education